An operando DRIFTS study of the active sites and the active intermediates of the NO-SCR reaction by methane over In,H- and In,Pd,H-zeolite catalysts - Lónyi, Ferenc (2010)
Zeolites In,H-ZSM-5 (Si/Al=29.7, 1.7wt% In) and In,H-mordenite (In,H-M, Si/Al=6.7, 3.5 wt% In) were prepared by reductive solid state ion exchange (RSSIE) method and studied in the selective catalytic reduction of NO (NO-SCR) by methane. The results suggested that the methane oxidation reactions proceed by redox type mechanisms over In+/InO+ sites. The NO reduction selectivity was shown to be related to the relative rates of In+ oxidation by NO and O2. Regarding the relative rates, the In+ density of the zeolite was the most important. Above about 673K the In,H-ZSM-5 (T-atom/In=102) had higher NO reduction selectivity than the In,H-mordenite (T-atom/In=46). The operando DRIFTS examinations suggested that NO+ and NO3 - surface species were formed simultaneously on InO+Z- sites, and were consumed together in the NO-SCR reaction with methane. The reduction of the NO3 - by methane gave an activated N-containing intermediate, which further reacted with the NO+ species to give N2. The NO-SCR properties could be significantly improved by adding small amount of Pd to the In,H-zeolite catalyst. The promoting effect of Pd was interpreted as a concerted action of InO+ and the Pdn+ sites. The interplay between these sites is twofold: the Pd speeds up the equilibration of the NO/O2 mixture, thereby, increases the formation rate and the steady state concentration of the activated nitrate species, whereas the In+/InO+ sites prevent the transformation of Pd-nitrosyls to less reactive isocyanate and nitrile species.